Trypanosoma cruzi infection, discrete typing units and feeding sources among Psammolestes arthuri (Reduviidae: Triatominae) collected in eastern Colombia (2019)
Background: Chagas disease (CD) is caused by the protozoan parasite Trypanosoma cruzi, and is transmitted by hematophagous insects of the family Reduviidae. Psammolestes arthuri is a sylvatic triatomine distributed in Colombia and Venezuela which feeds on birds and there are a few studies that have reported Ps. arthuri naturally infected with T. cruzi. In Colombia, Ps. arthuri has been found in dwellings, making it important to evaluate its possible role in the T. cruzi transmission cycle. We aimed to evaluate the presence of T. cruzi and feeding sources of Ps. arthuri to elucidate new possible scenarios of T. cruzi transmission in the country. Methods: A total of 60 Ps. arthuri were collected in Arauca and Casanare, Colombia. We detected and genotyped T. cruzi and identified feeding sources. The frequency of the presence of T. cruzi was obtained and compared with different eco-epidemiological variables. Multiple correspondence analysis was conducted to explore associations between eco-epidemiological variables and the presence of T. cruzi; with these results, a logistic regression was used to determine statistical associations. Results: The infection rate of T. cruzi was 70.7% and was mostly associated with insect stage, sex, bird nest and feeding source. Regarding discrete typing units (DTUs), TcI was found in 54.7% samples, of which 21.7% (5/23) were TcI Dom , 52.1% (12/23) had mixed infection (TcI Dom -TcI Sylv ), and single infection with TcI Sylv was not detected. Mixed infections (TcI/TcII-TcVI) were found in 9.52% (4/42) of the samples; of these, 14.2% (6/42) were TcII-TcVI. A total of 15 feeding sources were identified and the most frequent were: Cranioleuca baroni (35.85%), Homo sapiens (26.42%), Thraupis episcopus (11.32%) and Serinus albogularis (3.77%). Conclusions: Although Ps. arthuri is mainly ornithophilic, this species may be feeding on other animals that can be infected with T. cruzi, possibly playing a role maintaining the zoonotic cycle of the parasite. Further studies with molecular techniques and wider sampling are needed to improve information regarding infection rates, ecotopes and habits with the aim of evaluating whether Ps. arthuri could be a potential T. cruzi vector. © 2019 The Author(s).